2012
DOI: 10.1007/s00425-012-1798-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of barley leaf proteome as affected by drought stress

Abstract: The adaptive response of Egyptian barley land races to drought stress was analyzed using difference gel electrophoresis (DIGE). Physiological measurements and proteome alterations of accession number 15141, drought tolerant, and accession number 15163, drought sensitive, were compared. Differentially expressed proteins were subjected to MALDI-TOF-MS analysis. Alterations in proteins related to the energy balance and chaperons were the most characteristic features to explain the differences between the drought-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 58 publications
4
74
1
1
Order By: Relevance
“…Although such approach is correct and gives clues about differences in the response of such plants, the tolerance level is very often determined only according to physiological traits. Usually the following parameters are measured: relative water content (RWC), water loss rate (WLR) (WendelboeNelson and Morris 2012), value of fast chlorophyll fluorescence analysis (Ashoub et al 2013), photosynthesis rate, shoot and root length and fresh weight (Kausar et al 2013). Obviously, such analyses provide information about the differences in resistance to abiotic factors between the genotypes, but if the studied plant is a crop species, its crop yield should also be measured and taken into consideration while determining the tolerance level (Verslues et al 2006;Dolferus et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although such approach is correct and gives clues about differences in the response of such plants, the tolerance level is very often determined only according to physiological traits. Usually the following parameters are measured: relative water content (RWC), water loss rate (WLR) (WendelboeNelson and Morris 2012), value of fast chlorophyll fluorescence analysis (Ashoub et al 2013), photosynthesis rate, shoot and root length and fresh weight (Kausar et al 2013). Obviously, such analyses provide information about the differences in resistance to abiotic factors between the genotypes, but if the studied plant is a crop species, its crop yield should also be measured and taken into consideration while determining the tolerance level (Verslues et al 2006;Dolferus et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The comparative analysis of barley leaves subjected to drought stress revealed the upregulation of HSP100, HSP90 in both sensitive and tolerant genotype. A member of HSP70 was found to be down-regulated only in the sensitive genotype (Ashoub et al 2013). In the study conducted by Kausar and co-workers, HSP70 was also down-regulated in drought-sensitive barley (Kausar et al 2013).…”
Section: Heat Shock Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…In wheat and barley, transcript, protein, metabolite profi ling studies conducted in the last couple of years are shown in Table 17.3 . For example, changes in protein profi le of barley in response to drought stress were analyzed using a proteomics technique (Kausar et al 2013 ;Ashoub et al 2013 ). Alterations in proteins related to the energy balance and chaperons were the most characteristic features to explain the differences between the drought-tolerant and the drought-sensitive accessions.…”
Section: Proteins and Genes Associated With Drought Tolerancementioning
confidence: 99%